2010
DOI: 10.5694/j.1326-5377.2010.tb03531.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of chemotherapy and radiotherapy in patients with pancreatic cancer in Victoria (2002–2003): a retrospective cohort study

Abstract: Objective: To describe the management and outcomes of a population‐based cohort of patients with pancreatic cancer treated with chemotherapy or radiotherapy in Victoria, Australia. Design, setting and patients: Questionnaire‐based study of patients diagnosed with pancreatic cancer during 2002–2003 in Victoria who were retrospectively identified from the Victorian Cancer Registry and followed up for a minimum of 5 years. Main outcome measures: Reported treatment, referral patterns and survival rates. Results: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…The proportion of patients for whom chemotherapy is prescribed has increased in recent years in our state. A Victorian study of patients treated between 2002 and 2003 observed that 185 of 578 (32%) of patients with advanced disease had received palliative chemotherapy, 11 compared with 54% in our study (2016–2019). In the 2002–2003 study, 15% of patients initially considered for chemotherapy did not proceed with treatment, the major contributing reason being patients declining the offered treatment, followed by disease progression and functional decline.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The proportion of patients for whom chemotherapy is prescribed has increased in recent years in our state. A Victorian study of patients treated between 2002 and 2003 observed that 185 of 578 (32%) of patients with advanced disease had received palliative chemotherapy, 11 compared with 54% in our study (2016–2019). In the 2002–2003 study, 15% of patients initially considered for chemotherapy did not proceed with treatment, the major contributing reason being patients declining the offered treatment, followed by disease progression and functional decline.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, neither olaparib in the maintenance setting nor nanoliposomal irinotecan in the second‐line setting is currently reimbursed in Australia. Prior to the advent of combination regimens, chemotherapy was prescribed in only one‐third of patients in our state, Victoria 11 . Our study seeks to establish current practice in Australia and subsequent survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One Australian cohort observed that 43 % of the patients received palliative chemotherapy; however, this was a smaller study with 1863 patients and selection bias may have occurred (Burmeister et al 2015 ). A second Australian study by Jefford et al ( 2010 ) reported 54 % chemotherapy use, but analyzed both resectable and irresectable patients. A recent study by Oberstein et al ( 2013 ) seems to report a considerably higher percentage of patients treated with palliative chemotherapy (54 %).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined administration frequencies of specific chemotherapeutic regimens and the predictors of their usage in MPC . Existing literature consists of research conducted in limited practice settings or studies with data derived from retrospective medical record extraction , patient and physician surveys , or insurance claims to ascertain use . To understand factors influencing treatment decisions, we analyzed data from a nationwide, commercially available chemotherapy order entry (COE) system that provided tumor stage, disease status and treatment indication.…”
Section: Introductionmentioning
confidence: 99%